Bone Mineral Density of Very Long-term Survivors After Childhood Liver Transplantation. Issue 5 (May 2018) - Ee, Looi C.; Noble, Charlton; Fawcett, Jonathan; Cleghorn, Geoffrey J.
ABSTRACT: Objectives: Liver transplant patients are at risk of osteopenia and fractures but limited information is available in long-term survivors after childhood transplantation. This study aimed to assess bone mineral density (BMD) of very long-term, >5 years, survivors after liver transplantation in childhood. Methods: Patients aged <18 years at transplant, having survived >5 years after transplant were potentially eligible but only those with ongoing review in our state were included. Dual-energy x-ray absorptiometry (DXA) was used to measure BMD. Patients aged <20 years had lumbar spine (LS) and total body (TB) measurements whereas those aged 20 years or more had LS and femoral neck but not TB. BMD z -scores for LS and TB, if available, were used in this study. BMD z -score ⩽−2.0 was considered reduced. Pre-pubertal children had radiologic bone age assessment. Results: Forty-two patients, 17 boys, participated of whom 64% had biliary atresia. Median age at transplant was 2.22 (range 0.38–14.25) years; time since transplant 10.10 (5.01–25.98) years; and age at DXA 14.64 (6.59–38.07) years. Mean BMD z -scores were LS −0.15 ± 1.07, and TB −0.76 ± 1.14, with no sex difference noted. Four (9.5%) patients had reduced LS BMD, and although ongoing steroid use was more frequent in these patients, other comorbidities were likely important. Age at transplant, time since transplant, height, weight, and body mass index at DXA did not predict LS BMD. Pathologic fractures occurred in 2 of 42 (5%) patients; all within 18 months of transplant. Conclusions: Very long-term survivors after childhood liver transplant have LS BMD within the normal range.